Hubungan Upaya Guru Mendisiplinkan Siswa dengan Tingkat Kedisiplinan Siswa - Eltry Pratami Almezanda; Dina Sukma (MASALIQ, 2024)
This research is based on the existence of students who lack discipline and violate school rules. One of the factors that influences student discipline is the teacher's efforts. This research aims to: (1) describe students' perceptions of teachers' efforts to improve student discipline at SMP Negeri 11 Padang. (2) describe student discipline at SMP Negeri 11 Padang. (3) find out whether there is a relationship between students' perceptions of teachers' efforts to improve discipline and student discipline at SMP Negeri 11 Padang. This research uses quantitative research methods with a descriptive approach. The population of this research was 700 students at SMP Negeri 11 Padang for the 2024/2025 academic year with a research sample of 265 students selected using stratified random sampling. Data were analyzed using descriptive statistical techniques and Pearson Product Moment correlation. The results of this research indicate that the level of student discipline at SMP Negeri 11 Padang is in the high category, the teacher's efforts to discipline students at SMP Negeri 11 Padang are in the good category, and there is a positive and significant relationship between the teacher's efforts to discipline students (X) and the level of discipline student (Y) at SMP Negeri 11 Padang with a correlation coefficient of 0.756 with a significance value of 0.000 at a strong relationship level.